2015
DOI: 10.1002/cite.201400075
|View full text |Cite
|
Sign up to set email alerts
|

Development of Micro Separation Technology Modules. Part 2: Distillation

Abstract: The subject of previous work on liquid‐liquid extraction is complemented in this paper through the research activities in micro distillation. After a detailed literature study comparing the performance, strengths, and weaknesses of published micro distillation methods, critical process parameters based on model studies will be discussed. Apparative approaches to micro distillation are presented, where the capillary module used for distillation can provide a successful phase separation of gas‐liquid mixtures up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 29 publications
0
3
0
2
Order By: Relevance
“…The micro applications for distillation can be classified according to the functional principle. Further studies on micro distillation can be found in , . The principle of the falling film apparatus is described in .…”
Section: Separationmentioning
confidence: 99%
“…The micro applications for distillation can be classified according to the functional principle. Further studies on micro distillation can be found in , . The principle of the falling film apparatus is described in .…”
Section: Separationmentioning
confidence: 99%
“…The performance of the micro-distillation systems described above is fundamentally dependent on the heat transfer efficiency and temperature distribution within the microfluidic device. Accordingly, many researchers have employed numerical simulation methods to optimize the performance of micro-distillation systems [ 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. For example, Stanisch et al [ 38 ] conducted numerical simulations to investigate the effects of the primary processing parameters (e.g., the reflux ratio, evaporation rate, and choice of feed stage) on the performance of a micro-distillation system intended for the separation of ethanol/water feed streams.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, many researchers have employed numerical simulation methods to optimize the performance of micro-distillation systems [ 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. For example, Stanisch et al [ 38 ] conducted numerical simulations to investigate the effects of the primary processing parameters (e.g., the reflux ratio, evaporation rate, and choice of feed stage) on the performance of a micro-distillation system intended for the separation of ethanol/water feed streams. Overall, the results presented in [ 37 , 38 ] confirmed that numerical simulations provide a versatile and effective approach for the design, characterization, and optimization of microfluidic distillation systems.…”
Section: Introductionmentioning
confidence: 99%
“…Em sistemas convencionais, a gravidade é usada para conduzir a fase líquida para baixo e a fase vapor é impulsionada para cima pela diferença de pressão a fim de produzir o contrafluxo requerido. Nos microcanais, as forças de superfície, como viscosidade, capilaridade e tensão superficial, predominam sobre as forças gravitacionais 9,[35][36][37][38][39][40][41][42][43] , o que impede que a separação das fases ocorra como na macroescala. Consequentemente, alternativas são desenvolvidas para a separação de fases, condução e coleta de vapor dentro desses sistemas, quais sejam, uso de gás de arraste e de vácuo, força centrífuga e força capilar.…”
Section: Sistemas De Destilação Miniaturizadosunclassified
“…Embora diversos destiladores miniaturizados já tenham sido reportados na literatura 9,[31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] , ainda não houve a aplicação desses microssistemas para a destilação de petróleo haja vista a complexidade da amostra. Além disso, a miniaturização desse processo não é simples devido a uma série de desafios, os quais incluem: i) condições experimentais severas (amostras orgânicas em temperaturas altas); ii) incorporação de vários componentes (termopares, coluna de fracionamento, condensador e canais para introdução da amostra e coleta do destilado) em um dispositivo compacto; iii) manutenção da temperatura ideal na coluna e iv) necessidade de monitorar as temperaturas em diferentes pontos do sistema (amostra, coluna e coleta do destilado).…”
Section: Introductionunclassified